The Conservationist Principle under International Humanitarian Law versus a Transformative Occupation in a Human Rights Context - Maria Helena Carbonell Yánez (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
AbstractThis article presents a discussion about the necessary evolution of the law of occupation facing the obligations set for by the International Human Rights regime, based on the law of State responsibility. In the first section of this two-part study, the article delivers a state of the art through the analysis of doctrine and both universal and regional jurisprudences on State responsibility based on the extraterritorial application of International Human Rights Law. On the second part, the article provides analysis on temporal (beginning and end) and territorial aspects of occupation that have a direct impact on the obligation to respect and to ensure the rights of every subject to the State’s jurisdiction. In the final section, the article discusses the clash between the traditional conservationist principle and the transformative occupation principle. This study employed a logic-inductivist method. To conclude the discussion, this study is in the position that the conservative principle under International Humanitarian Law is considered archaic; and should give way to better protection of human rights in an international occupation context.Prinsip Konservasionis dalam Hukum Humaniter Internasional vs. Okupasi Transformatif dalam Konteks Hak Asasi ManusiaAbstrakArtikel ini menyajikan diskusi tentang perkembangan hukum okupasi dalam menghadapi kewajiban yang ditetapkan oleh rezim Hukum HAM Internasional, berdasarkan tanggung jawab negara. Bagian pertama artikel membahas tentang keadaan terkini melalui analisis doktrin dan yurisprudensi universal dan regional terhadap tanggung jawab negara berdasarkan penerapan asas ekstrateritorial dalam Hukum HAM Internasional. Bagian kedua penulis menganalisis aspek temporal dan teritorial dalam okupasi yang memiliki dampak langsung pada kewajiban untuk menghormati hak-hak setiap individu yang tunduk pada yurisdiksi negara. Pada bagian terakhir, artikel ini membahas tentang perbedaan antara prinsip konservasionis tradisional dengan prinsip okupasi transformatif. Melalui metode logic-inductivist, artikel ini menyimpulkan bahwa prinsip konservasionis dalam kerangka Hukum Humaniter Internasional telah ketinggalan jaman dan upaya lain harus dilakukan untuk memberikan perlindungan HAM yang lebih baik ketika okupasi internasional terjadi.DOI: https://doi.org/10.22304/pjih.v6n1.a2